Efektivitas Model Pembelajaran TGT Berbantuan Engklek Eduflex dalam Meningkatkan Pemahaman Konsep Matematika Siswa SD - Yulfani, Siswi; Putra, Lisa Virdinarti (MASALIQ, 2025)
This study aims to analyze the impact of the Team Games Tournament (TGT) cooperative learning model, supported by the Engklek Eduflex medium, on the conceptual understanding of mathematics among fifth-grade elementary students. TGT is a cooperative learning model designed to enhance student interaction through engaging and competitive group activities. The addition of Engklek Eduflex, a modified traditional game, is expected to strengthen learning outcomes by connecting familiar play elements with educational objectives. The research employs a quasi-experimental design with pretest-posttest assessments on two groups: an experimental group using TGT with Engklek Eduflex and a control group using TGT alone. The findings reveal that TGT supported by Engklek Eduflex significantly improves students' conceptual understanding of mathematics compared to the control group. The Engklek Eduflex medium proves effective in creating a fun learning environment, enhancing students’ interest and engagement in the learning process.